(untitled) (Community Based Medical Journal, 2024)
A cross-sectional, observational study was conducted in the Department of Obstetrics and Gynaecology at Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, to evaluate the indications and feto-maternal outcomes of Caesarean section operation among preterm pregnant women. A total of 120 patients were enrolled between January and December of 2023. Data collection involved a structured questionnaire, file review, historical inquiry, and monitoring of mother and baby. Most individuals were aged 15-20 (37.50%) and had tertiary education (75.00%). Majority were from poor socio-economic backgrounds (76.67%) and rural areas (70%). Primigravida cases were predominant (65.00%), and multiparous accounted for 36.67%. Eclampsia (21.67%) and preeclampsia (20.83%) were common indications for cesarean section. Most procedures were emergency (93.33%). Maternal complications were low, with 64.17% having none. Most infants had low birth weight (62.50%) and experienced live births (91.67%), with a notable stillbirth rate (8.33%). Fetal complications included low birth weight (88.33%) and prematurity (20%). No complications were noted in 31.67% of cases. The study examined the complexities of Cesarean section (CS) for preterm births, highlighting maternal-fetal factors, varied indications, and outcomes, urging tailored interventions. CBMJ 2024 July: vol. 13 no. 02 P: 243-250